SERVICE QUALITY ANALISYS OF ‘TABLE8’ CHINESE RESTAURANT AT THE MULIA, MULIA RESORT AND MULIA VILLAS - Lia Lisnawati; I Putu Astawa (Journal of Applied Sciences in Travel and Hospitality, 2020)
This study is analyze about service quality analisys of Table8 chinese restaurant at The Mulia. The purposes of this research are to know the service quality of Table8 Chinese Restaurant staff to customer satisfaction and to know the indicator that must be improved and maintain the quality of service performed by the Table8 Chinese Restaurant staff at The Mulia. The number of samples were 60 respondents, with the data collecting method was incidental sampling. Primary data collection of quality of service variable use questionnaire method with validity and reliability tested. The analysis technique use Servqual analysis and Importance Performance Analysis presented in Cartesian Diagram. The results of this research showed that there are negative, positive and neutral gap between perceptions and customer expectations. The customers are satisfied because the value of positive gap more than negative gap. Meanwhile in the technique Importance Performance Analysis the indicator in improving service quality performed by Table8 Chinese Restaurant staff at the Mulia are: strategic location of restaurant and easy to access, Ability to the restaurant staff to provide accurate information. Then, restaurant staff ability to handle guest’s complaints. And the indicator that must be maintained service quality are: politeness and friendliness of the restaurant staff, Ability restaurant staff in providing properly table service, restaurant staff in given individual attention to the guest. Table8 Chinese Restaurant should prioritize and improve the performance of these indicators in order to enhance the service quality of Table8 Chinese Restaurant staff for maximizing the customer satisfaction.